Description of Patient Satisfaction with the Cleanliness of the Hajj General Hospital Makassar - Ibrahim, Irviani Anwar (Universitas Islam Negeri Alauddin Makassar, 2025)
Islamic hospitals are a form of Islamic health business that has an important role in providing health services to the community. One of the important aspects of hospital services is the cleanliness of the house according to the standards that have been set for the comfort of patients and institutions at the hospital. This study aims to provide an overview of patient satisfaction with hospital cleanliness at RSUD Haji Makassar. This research uses a qualitative method with a descriptive analysis approach, which collects data by interviewing and making direct observations regarding hospital cleanliness. The research results show that RSUD Haji has good hygiene standards as proven by patient testimonies and direct incidents when we made direct observations.